Muscle oxigenation during different intensity and duration of time training sessions in world-class kayak rowers - Dadeliene, R.; Nekriošius, R.; Dadelo, S. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Aerobic metabolism processes in muscles play essential role in 1000 m. distance for kayak rowers` work. Interval training method is used as one of the means of training methods, applied for kayak rowers training. Therefore, the aim of the study was to explore an effect of different intensity and duration of time training workouts for world-class kayak rowers` (500 and 1000 m.) muscle oxygenation.